Design optimisation of 3D woven reinforcements with geometric features - Yan, Shibo (2017)
3D weaving technology enables the manufacturing of advanced near net-shape profiles, through incorporating geometric features such as bifurcations, and varying cross-sections into the preform, for use as reinforcements in composite materials. Their design space is very large due to a wide range of weave patterns in their 3D fibre architectures, and currently the lack of analysis techniques that relate weave architectures with the resulting processing and structural performance restricts the application of such advanced 3D woven composites.